Experimental testing on plastic hinge formation for steel beams : distribution of stress and spread of plastic hinge - Tay, Bernard Shing Ann. (2012)
In Structural Steel Design, members are commonly designed to withstand load up to the yield stress of the material. However with the incorporation of safety factors, it is not common for structural steel members to achieve the yield stress throughout their service lifetime. The safety factors are present in the specified design strength of the material that is obtained with the mill certificate from the manufacturer, the application of material partial factor of safety coefficients in the design codes as well as material factor of safety present in the design formulas. It is therefore uncommon for the steel material to be subjected to stresses that are large enough to cause the development of plastic hinges. However, it is of importance to study and understand the behavior of plastic hinge formation in steel members in light of unexpected external loadings such as earthquake loads and blast loads.